Tools for self- or peer-assessment of interprofessional competencies of healthcare students: a scoping review - Brownie, Sharon; Yap, Jia Rong; Blanchard, Denise; Amankwaa, Issac; Pearce, Amy; Sampath, Kesava Kovanur; Yan, Ann-Rong; Andersen, Patrea; Broman, Patrick (Frontiers in Medicine, 2024)
Introduction Healthcare professionals are expected to demonstrate competence in the effective management of chronic disease and long-term health and rehabilitation needs. Care provided by groups of collaborating professionals is currently well recognized as a more effective way to support people living with these conditions than routine, single-profession clinical encounters. Clinical learning contexts provide hands-on opportunities to develop the interprofessional competencies essential for health professional students in training; however, suitable assessment tools are needed to support student attainment of interprofessional competencies with self-assessment espoused as an important component of learning. Method A structured approach was taken to locate and review existing tools used for the self-assessment and peer assessment of students’ competencies relevant to interprofessional practice. Results A range of self- and/or peer assessment approaches are available, including formally structured tools and less structured processes inclusive of focus groups and reflection. Discussion The identified tools will usefully inform discussion regarding interprofessional competency self- and peer assessment options by healthcare students participating in a broad range of clinical learning contexts. Conclusion Self- and/or peer assessment is a useful approach for those seeking to effectively enhance interprofessional learning and measure the attainment of related competencies.